Penatalaksanaan Fisioterapi dengan Pendekatan Neuro Development Treatment pada Kasus Cerebral Palsy Spastic Athetoid Quadriplegi Di PNTC Karanganyar - Widiyas Tuti, Retno (2017)
Background: Cerebral Palsy is a wide term that include some abnormallities and damage in neurologic that occur a birth or in early infacy. Cerebral Palsy spastic athetoid quadriplegi is a condition that is shown by the presence of symetric disorders in the forth extremities characteriezed by there is a of hipertonus or hypotonus in muscle and has of a real spasticity value. Modality of physiotherapy used for the method of Neuro Development Treatment (NDT). Objective: To know the management of Physiotherapy in Cerebral Palsy Spastic Athetoid Quadriplegi case in controlling or decreasing the level od spasticity and improving functional ability. Result: After 6 times therapy obtained the result (1) fixed spasticity from TI to T6 as measured by Modified Asworth Scale, on the shoulder obtained value 1, on the wrist obtained value 2, and on the elbow, hip, knee and ankle obtained value 3 (2) functional capabilities as measured with GMFM from TI to T6 obtained a total fixed result of 1,56 %. Conclusion: Management of physiotherapy using Neuro Development Treatment (NDT) on Cerebral Palsy Spastic Athetoid Quadriplegi conditional in contolling the spasticity level and improving functional ability has not significant changes.